Transactional framework of sharecropping: empirical evidence - Chew, Tek Ann (Elsevier Science, 1998)
Chew [Chew, Tek-Ann, 1991. Share contracts in Malaysian rubber smallholdings. Land Econ., 67: 85–98; Chew, Tek-Ann, 1993. The Transactional framework of sharecropping: further implications. Can. J. Agric. Econ., 41: 209–221.] proposed a transactional framework of sharecropping that accommodates both the Marshallian and the Cheungian equilibria. An important conclusion arising thereof is the hypothesis that Cheung's sharecropping equilibrium is the rarity while the Marshallian equilibrium is the norm. In this paper, we collated some recent evidences to verify this hypothesis. The evidences support the Marshallian equilibrium, thereby providing indirect support for the transactional framework of sharecropping.